Transcription Factor KLF10 Constrains IL-17-Committed Vγ4+ γδ T Cells - Kim, Girak; Gu, Min Jeong; Kim, Soo Ji; Ko, Kwang Hyun; Kye, Yoon-Chul; Kim, Cheol Gyun; Cho, Jae-Ho; Lee, Woon-Kyu; Song, Ki-Duk; Chu, Hyuk; Park, Yeong-Min; Han, Seung Hyun; et al. (Frontiers in Immunology, 2018)
γδ T cells, known to be an important source of innate IL-17 in mice, provide critical contributions to host immune responses. Development and function of γδ T cells are directed by networks of diverse transcription factors. Here we examine the role of the zinc finger transcription factor, Kruppel-like factor 10 (KLF10), in the regulation of IL-17–committed CD27- γδ T (γδ27--17) cells. We found selective augmentation of Vγ4+ γδ27- cells with higher IL-17 production in KLF10-deficient mice. Surprisingly, KLF10-deficient CD127hi Vγ4+ γδ27--17 cells expressed higher levels of CD5 than their wild-type counterparts, with hyper-responsiveness to cytokine, but not T-cell receptor, stimuli. Thymic maturation of Vγ4+ γδ27- cells was enhanced in newborn mice deficient in KLF10. Finally, a mixed bone marrow chimera study indicated that intrinsic KLF10 signaling is requisite to limit Vγ4+ γδ27--17 cells. Collectively, these findings demonstrate that KLF10 regulates thymic development of Vγ4+ γδ27- cells and their peripheral homeostasis at steady state.